2012
DOI: 10.1366/11-06524
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Binding of 2-Aminobenzothiazole with Human Serum Albumin (HSA): Spectroscopic Investigation and Molecular Modeling Studies

Abstract: As one of the important thiazole derivatives, 2-aminobenzothiazole (2-ABT) has been widely used as a structural unit in the synthesis of anti-oxidants, anti-inflammatories, herbicides, antibiotics, and thermoplastic polymers. In this study, the interaction of 2-ABT with human serum albumin (HSA) was investigated in vitro under simulated physiological conditions, using multi-spectroscopic techniques and a molecular modeling study. The binding constant and binding sites were determined through fluorescence quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Static quenching of BSA as induced by the metal complexes was confirmed by the obtained k q values. The latter is also supported by the characteristic UV‐Vis spectral changes in the UV‐Vis profile of BSA upon addition of the individual metal compounds [36c,40a,42] . Other ruthenium compounds in literature have reported similar K SV and k q values, e. g .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Static quenching of BSA as induced by the metal complexes was confirmed by the obtained k q values. The latter is also supported by the characteristic UV‐Vis spectral changes in the UV‐Vis profile of BSA upon addition of the individual metal compounds [36c,40a,42] . Other ruthenium compounds in literature have reported similar K SV and k q values, e. g .…”
Section: Resultssupporting
confidence: 61%
“…The latter is also supported by the characteristic UV‐Vis spectral changes in the UV‐Vis profile of BSA upon addition of the individual metal compounds. [ 36c , 40a , 42 ] Other ruthenium compounds in literature have reported similar K SV and k q values, e. g . the ruthenium(II) compounds, [Ru(bpy) 2 smp](PF 6 ) (bpy=2,2’‐bipyridine, smp=sulfamethoxypyridazine) and [Ru( η 6 ‐ p ‐cymene)(diclo)Cl] (Hdiclo=2‐[(2,6‐dichlorophenyl)amino]benzeneacetic acid) possessed K SV values of 1.02×10 5 M −1 and 6.45×10 4 M −1 , respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Circular dichroism is a very sensitive technique, frequently used to monitor even minor conformational changes in protein upon binding to ligands [2b,13,39]. The CD spectra of native HSA in phosphate buffer solution at pH 7.4 was recorded and showed two negative bands at 208 nm and 222 nm indicative of π–π* and n–π* transfer of the peptide bond in the α‐helical structure of the protein [4b,40]…”
Section: Resultsmentioning
confidence: 99%
“…Considerable numbers of studies on the most precise interaction of HSA and small ligands have been reported so far . Our research group has been working on the design and synthesis of new antimalarial compounds, single crystal structure analysis and, most recently, on interaction studies of small molecules with serum albumin.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results of kaffir lime juice can be as well compared with the interaction of HSA with one of the essential thiazole derivatives, 2-amino benzothiazole (2-ABT), which is widely used as a structural unit in the synthesis of antioxidants, anti-inflammatories, herbicides, antibiotics, and thermoplastic polymers. The interaction of 2-ABT with HSA under simulated physiological conditions by three-dimensional (3D) fluorescence showed high binding and fluorescence quenching spectra properties [52].…”
Section: Fluorescence Properties Of Kaffir Lime Juicementioning
confidence: 99%